SURVEI MOTIVASI ATLET KARATE DI KABUPATEN OGAN ILIR USIA 16-19 - Almaragi Almaragi; Destriana Destriana; Silvi Aryanti (Ilmu Olahraga, 2023)
The purpose of this study was to determine the motivation of karate athletes in Ogan Ilir Regency aged 16-19 years. This research belongs to the type of quantitative descriptive research. The method in this study is a survey method. The sample used was karate athletes from Ogan Ilir Regency totaling 20 athletes consisting of male and female athletes with an age range of 16-19 years. The instrument to measure motivation is the sport motivation scale-6 (SMS-6). The results showed that the motivation of karate athletes in Ogan Ilir Regency Age 16-19 with the greatest frequency was high motivation with a total of 7 athletes with a percentage of 35%, in the moderate motivation category with 8 athletes had a percentage of 40% and low motivation only 5 athletes with a percentage of 25 %. The findings in this study are that the 1619 year old karate athletes in Ogan Ilir Regency have moderate motivation. The implementation of the results of this study is that athletes can find out their level of motivation so that in the future both coaches and administrators or the athletes themselves can implement an appropriate training program.